Performance of the professional councils concerning 966 complaints addressed to Regional Councils of Medicine (CRM) of Minas Gerais from 2012 to 2017 - Nogueira Gonçalves, Eduardo Luiz; Lima e Silva, Francisco das Chagas; Rego, Guilhermina (Acta Bioethica, 2022)
The study aimed to analyze the actions of the Professional Councils in relation to 966 professional-ethical complaintsaddressed to the Regional Council of Medicine of Minas Gerais between 2012 and 2017. The number of cases, gender,articles violated of the Code of Medical Ethics and decisions made in the lawsuits were considered. An expressive result wasobserved in terms of acquittal (535 cases) by the Regional Council of Medicine of Minas Gerais. There was a divergence whenthe same cases were evaluated by the Federal Council of Medicine, which upheld the acquittal in only 29% of the cases. Dueto the methodology applied, it was not possible to go beyond speculation on the subject, being necessary a better analysis ofthe scientific community on this issue.